STUDIA FILOLOGICZNE, PRZYGOTOWANIE DO ZAWODU NAUCZYCIELA A WYZWANIA CODZIENNOŚCI - Pawlak, Mirosław (Neofilolog, 2019)
Becoming a foreign language teacher involves meeting a range of requirements which have mainly been specified in the Decree of the Minister for Science and Higher Education issued on January 17th, 2012, concerning the standards that have to be complied with in teacher education. Education of this kind is still most frequently offered in the course of BA or MA programs in foreign languages, with the crucial caveat that, primarily as a result of decreasing demand for foreign language teachers, this component has been eliminated in many institutions of higher education or students are required to pay for an additional module providing such training. It is assumed that on completion of a BA or MA program as well as obtaining credits for the required courses focusing on pedagogy, a student will have the requisite qualifications to teach a particular foreign language at appropriate educational levels. This implies that, by this time, he or she should have acquired the necessary knowledge, skills and competences, both in the foreign language and in psychological and pedagogical issues, which can ensure effective teaching and learning. The paper aims to subject such assumptions to critical scrutiny, demonstrate that they blatantly fail to take into account the real situation in Polish education, as well as offer some tentative proposals that could enhance the quality of foreign language teacher training in our country.